147: Pediatric Residents' Continuity Clinic: An Evaluation Survey. Issue 6 (1st June 2014) - Low, C; Carceller, A; Nguyen, P; Nguyen, B; Chabot, G; Jamoulle, O
Abstract: BACKGROUND: Training in ambulatory care and continuity of care has become an integral part of residency programs. Continuity clinics attempt to address these challenging aspects of medical education. Our centre has a long-standing paediatric residents' continuity clinic (PRCC) that had never been formally evaluated. OBJECTIVES: To assess resident satisfaction of their continuity clinic experience, before and after evidence-based improvements were made. DESIGN/METHODS: Cross-sectional surveys were conducted at a single paediatric training site in the academic years of 2012–2013 and 2013–2014 using online questionnaires. Our ethics committee approved this study. RESULTS: Most eligible residents participated in both questionnaires, of which around 60% had a high probability of becoming a general paediatrician. Residents had one monthly clinic; half the residents would increase this frequency. The majority had a mean of three to four appointments per session and in general they thought this was just enough. Before the study, 37% of residents were using standardised general follow-up tools, and 7% were using developmental screening tools. These figures only slightly improved at the time of the second questionnaire (48% and 8%). This is in the process of being formally addressed. Complex patients were perceived as being a difficult population to attend to within the settings of the PRCC, yet more than half the residents (55%) wished to see a greater number of complex patients. To attempt to facilitate this, PRCC patients became eligible to care coordination in our medical home program. Perception of teaching seemed to greatly improve during the study, becoming more consistent amongst preceptors. Teachers were generally perceived as being more enthusiastic and better acquainted with the resident following changes in the clinic's schedule. Evaluation was drastically improved; at the beginning of the study, one resident out of two had never been evaluated and 80% had never experienced direct observation of their ambulatory performance. In 2013–2014, the majority of residents had been evaluated (84%) and directly observed (56%). General resident satisfaction was also significantly enhanced; no resident said to be unsatisfied with the experience in the second questionnaire as opposed to 26% in the first. The overwhelming majority of residents agree that the continuity clinic is important in their training and for their future career. CONCLUSIONS: Residents highly value the continuity clinic educational experience; satisfaction markedly increased after improvements were made. These findings reiterate the importance of the continuity clinic model and the need for constant appraisal of this fundamental teaching opportunity.